Pediatric multiple sclerosis - Waubant, Emmanuelle; Chabas, Dorothee (Current treatment options in neurology, 2009)
Opinion statement The diagnosis of multiple sclerosis (MS) in a child remains challenging, given the limited diagnostic criteria and the somewhat poorly defined overlap with acute disseminated encephalomyelitis. Although there are many similarities between pediatric-onset and adult-onset MS, an earlier age at disease presentation seems to be associated with specific features such as more frequent encephalopathy, seizures, and brainstem and cerebellar symptoms during the first event. In addition, the initial brain MRI scan of younger patients shows more frequent involvement of the posterior fossa and higher numbers of ovoid, ill-defined T2-bright foci that often partially resolve on the follow-up scan, thereby challenging early diagnosis. Finally, the spinal fluid in younger patients may fail to reveal oligoclonal bands or elevated IgG index at disease onset. No therapy for MS in children has been approved by the US Food and Drug Administration. As a result, physicians have started to use off-label drugs approved for adults. Recent data suggest that some children experience a disease breakthrough on first-line therapies approved for adult MS, and thus second-line therapies must be considered.